2018
DOI: 10.29024/aogh.913
|View full text |Cite
|
Sign up to set email alerts
|

Potential Co-exposure to Arsenic and Fluoride and Biomonitoring Equivalents for Mexican Children

Abstract: Background:Mexico is included in the list of countries with concurrent arsenic and fluoride contamination in drinking water. Most of the studies have been carried out in the adult population and very few in the child population. Urinary arsenic and urinary fluoride levels have been accepted as good biomarkers of exposure dose. The Biomonitoring Equivalents (BE) values are useful tools for health assessment using human biomonitoring data in relation to the exposure guidance values, but BE information for childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 81 publications
2
23
0
1
Order By: Relevance
“…identified the Res-F as a predominant fraction 17,46,47 normally existing in mineral form and hardly bioavailable. 47 As regards to the WS-F, that together with the Ex-F is considered to form the labile and available soil fluoride pool, 48 values measured in the study area were from 2.7 to 5.5 times higher compared to those found by Dagnaw et al 44 being also always significantly higher than the threshold of 16.4 mg kg −1 of available fluoride in soil established by EPA, FAO, and WHO as cited by Lakshmi et al, 23 Limón-Pacheco et al 40 and Paul et al 41 Soil WS-F is highly related to the soil type: factors such as pH, clay minerals, organic matter and concentration of P and Ca are the main drivers of fluoride solubility in soil. Furthermore, in sodic soils, fluoride adsorption has been found to decrease with increasing exchangeable sodium percentage (ESP) level or pH.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…identified the Res-F as a predominant fraction 17,46,47 normally existing in mineral form and hardly bioavailable. 47 As regards to the WS-F, that together with the Ex-F is considered to form the labile and available soil fluoride pool, 48 values measured in the study area were from 2.7 to 5.5 times higher compared to those found by Dagnaw et al 44 being also always significantly higher than the threshold of 16.4 mg kg −1 of available fluoride in soil established by EPA, FAO, and WHO as cited by Lakshmi et al, 23 Limón-Pacheco et al 40 and Paul et al 41 Soil WS-F is highly related to the soil type: factors such as pH, clay minerals, organic matter and concentration of P and Ca are the main drivers of fluoride solubility in soil. Furthermore, in sodic soils, fluoride adsorption has been found to decrease with increasing exchangeable sodium percentage (ESP) level or pH.…”
Section: Discussionmentioning
confidence: 49%
“…Distribution of fluoride fractions in the soil Average concentrations of soil WS-F in the 0-40 cm layer in the three study areas ranged between four and eight times above the limit for available fluoride in the soil (16.4 mg kg −1 ) established by EPA, FAO, and WHO 23,40,41 ( Table 4). The concentrations of WS-F, Ex-F, Fe/Mn-F, OM-F and Res-F in the topsoil (0-20 cm) are illustrated in Fig.…”
Section: Resultsmentioning
confidence: 91%
“…On the other hand, the role of the microbiota in detoxification of xenobiotics and contaminants (pesticides and heavy metals) has been poorly studied. Nevertheless, it has been found that intestinal microbiota contributes to metabolism of xenobiotics [23] and heavy metals such as cadmium [21], mercury [20] and metalloids such as arsenic [24]. In this regards, in rats [53] and mice [54], several bacteria strains have been proposed and used as detoxifying probiotics, including mainly lactic acid bacteria.…”
Section: Microbiota and Its Compositionmentioning
confidence: 99%
“…Some factors that cause intestinal dysbiosis are antibiotics, alcohol consumption, infection of pathogenic microorganisms and diet [18], this last one can favor the proliferation of specific phyla of bacteria in the gut [19]. Likewise, gut dysbiosis has been associated to exposure to heavy metals as cadmium and mercury [20,21], halogenated compounds such as fluoride and metalloids such as arsenic, these last two contaminants of water for human consumption [22]. On the other hand, the role of the microbiota in the detoxification of xenobiotics [23], arsenic [24] and heavy metals [25], has been little studied.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in addition to as, these areas are overexposed to fluorides, and studies have reported synergy of fluorides and arsenic, with monitoring by water control organisms [7]. In Mexico there are areas exposed to as and fluoride.…”
Section: Introductionmentioning
confidence: 99%